2019
DOI: 10.1038/s41598-019-52360-w
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea (Vigna unguiculata (L.) Walp) for food security: an evaluation of end-user traits of improved varieties in Swaziland

Abstract: Improved varieties have agronomic advantages over local varieties,but not much attention has been given to understand the nutritional content of the improved cowpea varieties released in Swaziland. This study investigated the physical and nutritional properties of improved cowpea varieties released in Swaziland. Five improved varieties (IT-04K-321-2, IT-97K-390-2, IT-18, IT-16, and IT-99K-494-6) and one local variety (Mtilane, as check) were analyzed for physical and chemical properties. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 18 publications
2
35
2
2
Order By: Relevance
“…However, Gondwe et al . 55 focusing on V. unguiculata from Swaziland, found much lower contents of Ca, Fe, and Zn than the content found in our study, even for improved varieties. Content variation within the same species can be explained by several cross-related reasons: (i) the nutritional content of legumes can vary greatly and is highly dependent on soil fertility, which directly influences the supply and availability of most nutrient elements 56 ; (ii) the nutritional content is dependent and vary with different varieties and genotypes 46 , 57 ; and (iii) the nutritional content is influenced by preharvest conditions of the plant, maturity of the edible product at harvest and postharvest handling and storage conditions 58 .…”
Section: Discussioncontrasting
confidence: 95%
“…However, Gondwe et al . 55 focusing on V. unguiculata from Swaziland, found much lower contents of Ca, Fe, and Zn than the content found in our study, even for improved varieties. Content variation within the same species can be explained by several cross-related reasons: (i) the nutritional content of legumes can vary greatly and is highly dependent on soil fertility, which directly influences the supply and availability of most nutrient elements 56 ; (ii) the nutritional content is dependent and vary with different varieties and genotypes 46 , 57 ; and (iii) the nutritional content is influenced by preharvest conditions of the plant, maturity of the edible product at harvest and postharvest handling and storage conditions 58 .…”
Section: Discussioncontrasting
confidence: 95%
“…Our results revealed that ash contents ranged from 3.2% (Vigna unguiculata) to 4.1% (Phaseolus vulgaris), indicating that they are good sources of minerals (e.g., [47,48]). Moreover, all the studied species revealed an average moisture content ranging from 10.7 ± 0.2 g/100 g in Phaseolus vulgaris to 12.4 ± 0.9 g/100 g in Phaseolus lunatus and we concluded that it is possible to store all these beans with quality, in agreement with other studies (e.g., [49]).…”
Section: Chemical Compositionmentioning
confidence: 79%
“…Walp.) is an economically important crop legume in Africa, America and Asia [1][2][3]. This crop has five cultivar groups/subspecies including unguiculata (grain cowpea (also known as black-eye pea)), biflora, texilis, melanopthamus and sesquipedalis (yardlong bean (also known as asparagus bean)) [2,4].…”
Section: Introductionmentioning
confidence: 99%